Implementation of Business Model Canvas Development Based on Ngandel, Kendel, Bandel, Kandel to Overcome Marketing and Productivity Problems in Yogyakarta's Typical Jumputan Craft MSME - Pradana, Reza Yudha; Krisnawan, Andik Damar; Ramadhanti, Ardita Puri; Handayani, Laras Rizki; Wulandari, Hana; Kusumawardhani, Ratih (IJCS: International Journal of Community Service, 2024)
This community service was aimed at helping Sanggar Jumputan Maharani, founded by Mrs. Surani, in facing the challenge of declining sales, especially among young people. In addition, this service is a form of community service to introduce the business model canvas method and the application of Ki Hadjar's teachings in the business world. The approach used in this service is ethnography, where the researcher not only conducts interviews with several informants but also observations and participates in carrying out a series of production activities of Sanggar Jumputan Maharani UMKM such as observing, helping if needed during the production process, participating in the jumputan making process. From the results of interviews and observations obtained, the authors found various phenomena in internal and external factors. In addition, the author tried to provide Business Model Canvas training at Sanggar Jumputan Maharani which was used as a bridge to improve the marketing and productivity of these MSMEs. The results of the service showed that Sanggar Jumputan Maharani has its own advantages compared to other MSMEs. As well as superior in design, product quality and quantity, and the number of exhibitions that have been participated in. However, Sanggar Jumputan Maharani needs to increase the collection of motif designs according to supply and demand, as well as register the distinctive designs of Sanggar Jumputan Maharani in HAKI, as well as increase the number of human resources and increase jumputan production in order to reach more market segmentations with the Business Model Canvas method.